A Review Of CEM: Customer Engagement as Innovation Co-Creator - Elidjen Elidjen (ComTech: Computer, Mathematics and Engineering Applications, 2013)
Competition is very tight causing companies looking for a competitive edge, both in the product packaging and in maintaining good relations with their customers. The management of good relationship is commonly referred to Customer Relationship Management (CRM). In general, CRM is focused on how to market something to customers and obtain value from them by using information technology. However, it ignores customers’ insight that can provide added value to the company's profits. That is what causes the need for Customer Experience Management (CEM) to handle the experience of customers to improve value for customers so that customers become loyal. More useful definition of CEM is handling customer interactions to build brand equity and increase the long-term profitability. The five-element approach known as SMART (strategy, metrics; alignment, redesign and technology) has a positive impact for the company. In the end customers can actualize themselves, through a company's brand and products.